Effectiveness of Structured Teaching Programme on Knowledge Regarding Arterial Blood Gas Analysis among Nursing Students - Ghimire, Babita; Acharya, Anjana; Upadhyay, Hari Prasad (Journal of National Heart and Lung Society Nepal, 2023)
Background: Arterial blood gas (ABG) analysis measures blood pH, oxygen (O2), and carbon dioxide (CO2) levels. Normal pH is 7.35-7.45, PaO2 ranges from 70-100 mm Hg, PaCO2 is 35-45 mm Hg, and SaO2 is 93-98%. HCO3 normal value is 22-26 meq/l. This study assesses the effectiveness of a structured teaching program on arterial blood gas analysis knowledge among nursing students. Methods: A pre-experimental study with a one-group pretest-posttest design evaluated the effectiveness of a structured teaching program on Arterial Blood Gas analysis knowledge among nursing students from two Purbanchal University-affiliated colleges. Narayani Samudayik Nursing College was chosen using a probability-based simple random sampling lottery method. Enumerative sampling was employed to select respondents for the study. Results: The study found that 87% of respondents initially had an average knowledge level of arterial blood gas analysis, with 13% having adequate knowledge. After intervention, 82.6% demonstrated adequate knowledge, and 17.4% maintained an average level. Mean knowledge scores significantly increased from 67.15 to 87.7 in pretest and posttest, respectively (p<0.001). The results affirm the intervention’s effectiveness in improving participants’ understanding of arterial blood gas analysis.. Conclusion: Most respondents had average knowledge of ABG analysis. Following the structured teaching program, the majority achieved adequate knowledge, demonstrating its significant positive impact in enhancing nursing students’ unde standing of ABG analysis.